PENGARUH KETIDAKPASTIAN KEBIJAKAN EKONOMI TERHADAP PENGAMBILAN RISIKO PERUSAHAAN DI INDONESIA - Christhalia Severesia; Rita Juliana (Jurnal Riset Akuntansi dan Keuangan, 2022)
Abstract. Economic Policy Uncertainty which affects the risk-taking process in an enterprise is one of the crucial factors contributing to the sustainability and performance of the company. Government involvement also plays a major role in company risk-taking. This research was conducted to analyze the effect of economic policy uncertainty on the risk-taking decision in some companies in Indonesia. There are a total of 501 public companies listed on the Indonesia Stock Exchange from 2006 to 2020. Results of this study show that Indonesian companies tend to make low-risk decisions when economic policy uncertainty occurred. On the other hand, organizations with government ownership tend not to be influenced by the economic policy uncertainty Abstract. Economic Policy Uncertainty which affects the risk-taking process in an enterprise is one of the crucial factors contributing to the sustainability and performance of the company. Government involvement also plays a major role in company risk-taking. This research was conducted to analyze the effect of economic policy uncertainty on the risk-taking decision in some companies in Indonesia. There are a total of 501 public companies listed on the Indonesia Stock Exchange from 2006 to 2020. Results of this study show that Indonesian companies tend to make low-risk decisions when economic policy uncertainty occurred. On the other hand, organizations with government ownership tend not to be influenced by the economic policy uncertainty